2006
DOI: 10.1080/00288233.2006.9513711
|View full text |Cite
|
Sign up to set email alerts
|

Defining the relationships between pasture production and soil P and the development of a dynamic P model for New Zealand pastures: A review of recent developments

Abstract: A database was constructed comprising records from 2255 pasture phosphorus (P), potassium (K) and sulphur (S) field trials, of which 1799 included one or several rates of P. Subsets of this data were selected based on predetermined criteria to define the relationships between relative pasture production and available soil P (0-75 mm, Olsen P in µg P cm -3 soil)-the P production functions-for the major soil groups in New Zealand. These relationships, and their 95% confidence intervals, were defined using Bayesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 24 publications
(28 reference statements)
5
37
3
Order By: Relevance
“…97%RY) was c. 19 mg/ml. This Olsen P concentration is just below the average of 20 mg/ml derived for sedimentary soils (Morton & Roberts 2010) and less than the critical level for sedimentary soils of 26Á32 mg/ml reported by Edmeades et al (2006), but falls within the scatter of field trial results presented in their paper. Furthermore, work by Sinclair et al (1997) and Gillingham et al (2007Gillingham et al ( , 2008 showed that there is little advantage in sheep pastures of Olsen P concentrations greater than 20 mg/ml.…”
Section: P Response Curvessupporting
confidence: 67%
See 3 more Smart Citations
“…97%RY) was c. 19 mg/ml. This Olsen P concentration is just below the average of 20 mg/ml derived for sedimentary soils (Morton & Roberts 2010) and less than the critical level for sedimentary soils of 26Á32 mg/ml reported by Edmeades et al (2006), but falls within the scatter of field trial results presented in their paper. Furthermore, work by Sinclair et al (1997) and Gillingham et al (2007Gillingham et al ( , 2008 showed that there is little advantage in sheep pastures of Olsen P concentrations greater than 20 mg/ml.…”
Section: P Response Curvessupporting
confidence: 67%
“…5) Sinclair et al (1997) and Edmeades et al (2006). The relative yield of the RPR treated plots relative to the SSP asymptote are also presented in Fig.…”
Section: P Response Curvesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is somewhat surprising that an available P concentration of 18 μg ml −1 for the enriched CO 2 soil would limit plant growth. An analysis of a New Zealand P fertilizer trial database identified an Olsen P level of 12 μg ml −1 as a critical level for sandy soils, below which production would be reduced to less than 97% of relative yield (Edmeades et al 2006). Calibration of soil P levels and pasture production specific to the NZ FACE site would be needed to verify critical P levels for plant growth in this soil.…”
Section: Discussionmentioning
confidence: 99%